Creep feeding and phytohemagglutinin skin-test responses in pigs - Blecha, Frank; Pollmann, D.S.; VanWormer, D.M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
An experiment was conducted to determine the influence of creep feeding on cellular immunity in young pigs. Creep feeding from 10 days of age to weaning did not influence phytohemagglutinin skin-test responses.
Keywords: Swine; Creep feeding; Phytohemagglutinin skin-test